Integrated reporting and financial performance (evidence from Malaysia) / Luk Pui Wen, Angeline Yap Kiew Heong and Simon Lim Chee Hooi. - Luk, Pui Wen; Yap, Angeline Kiew Heong; Lim, Simon Chee Hooi (Accounting Research Institute (ARI), Universiti Teknologi MARA (UiTM), 2017)
Although the consciousness of Integrated Reporting (IR) is increasing within Malaysian companies, how IR creates value for their business is not completely understood. This paper attempts to investigate the potential contribution of IR implementation to the financial performance of the top 50 Malaysian public listed companies during the period of 2012 to 2015. The eight (8) IR content elements from the International Integrated Reporting Council (IIRC) framework are examined to predict the adoption rate of IR in relation to financial performance. This includes disclosure on organizational overview and external environment, governance, business model, risks and opportunities, strategy and resource allocation, performance, outlook, and basis of preparation and presentation. The data indicates that Malaysian PLCs reported more than 50% for every content element, except Basis of Preparation and Presentation (CE8).  Data analysis indicates that among the eight (8) content elements, four (4) of them, namely governance, business model, risks and opportunities, and performance disclosure, have significant positive impact on financial performances.  The finding of this paper provides insight into the contribution of IR in effecting the maintenance of business resilience and competitiveness in a fluctuating market. Therefore, this paper provides a significant impetus for implementation of IR among the Malaysian companies.